Hemovigilance data: An effective approach for evaluating bacterial protection systems for platelet transfusions - Meshari I. Alabdullatif (Asian Journal of Transfusion Science)
BACKGROUND AND OBJECTIVE: Septic transfusion reactions due to bacterial contamination in platelet concentrates (PCs) are continually reported to hemovigilance (HV) programs. Worldwide, blood centers use different systems to avoid transfusion-associated bacterial sepsis in PCs. Herein, national HV data were gathered to compare bacterial protection systems and to assess the risk of bacterial contamination. MATERIALS AND METHODS: HV data with definite transfusion-associated bacterial sepsis in PCs were obtained from Australia, Canada, the United Kingdom (U. K.), and Switzerland between 2006 and 2016. These data were reviewed to evaluate bacterial protection systems including early small-volume (ESV), early large-volume (ELV), and delayed large-volume (DLV) bacterial culture screening and pathogen inactivation (PI) treatment. RESULTS: Implementation of DLV bacterial culture screening in the U. K. and PI treatment in Switzerland resulted in significant reductions (P < 0.05) in transfusion-associated bacterial sepsis for the period of 2011–2016 compared to the prior 4 years (2006–2010). Approximately 1.86 million DLV bacterial culture-screened PCs and 0.21 million PI-treated PCs were issued with no reported septic fatalities nor cases of life-threatening sepsis. In Australia, two life-threatening septic transfusion reactions (1.923 per million) were reported out of almost 1.04 million ELV bacterial culture-screened PCs, and no septic fatalities were reported. Meanwhile, in Canada, four life-threatening septic transfusion reactions (3.6/million) and one fatality (0.9/million) were observed in about 1.11 million ESV bacterial culture-screened PCs. CONCLUSION: DLV bacterial culture and PI treatment significantly reduced the incidence of septic reactions. The advantages and disadvantages of both systems merit further investigation before implementation.